Intelligent System Stability using Type-2 Fuzzy Controller - D, Nagarajan; M, Lathamaheswari; Jacob, KaviKumar; E, Deenadayalan (International Journal of Integrated Engineering, 2019)
To avoid mathematical complexity, Interval T2FSs (IT2FSs) have been pertained in majority of the fields.Â Type-2 Fuzzy sets (T2FSs) handle a greater modelling and uncertainties which exist in the real world applications especially in control systems.Â One of the important components which influence the fuzzy controller is the triangular norms which are the aggregation operators. For getting the stability of a control system T Norm operator can be preferred. Gaussian Interval Type-2 Membership Function (GIT2MF) has been used in this paper. Also mathematical properties of aggregation operator are proved using Gaussian Interval Type-2 Weighted Arithmetic (GIT2WA) Operator. The aim of this work is analyzing the stability of an inverted pendulum using Interval Type-2 Fuzzy Logic controller (IT2FLC) and the results are compared with traditional Proportional Integrated Derivative (PID) Controller.Â It is observed that IT2FL controller gives better stability under imprecise condition.